PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL)UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 035 SEKELADI KECAMATAN TANAH PUTIH - Erfina '; Mahmud Alfusari; Lazim.N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the low learning outcomes fifth grade science students SD Negeri 035 Sekeladi, from the average value of students is 59.75. Of the 20 students who achieve above KKM only 8 (40%), while that has not reached the KKM 12 (60%), KKM predetermined is 70. The problems